SEMANTIC ANALYSIS OF DRAMATIC TERMS IN “THE CONCISE OXFORD DICTIONARY OF LITERATURE TERMS” (Scientific journal of the Fergana State University, 2023)
The scientific research shows that literary terms in the Germanic languages were not studied uniformly. The degree of study and significance of literary terms are carried out in the given article. The article also gives information about the dictionary of Chris Baldick “The Concise Oxford Dictionary of Literary Terms” and the significant aspects of literary terms. Terms belonged to the theory of literature, its history, process and dramatic works are discussed and the analyses of dramatic  terms given by Chris Baldick are explained in the article.